The Dependence of Prices and Volume - Rogalski, Richard J. (The Review of Economics and Statistics, 1978)
THE purpose of this paper is to empirically examine whether security prices and volume are causally related. Existing models that attempt to analyze the interdependence of price and volume in speculative markets have been generally built on basic underlying demand and supply conditions. Crouch (1970), Clark (1973), Westerfield (1973), and others have postulated that the absolute value of price change is positively and linearly related to volume. The rationale is that given an initial equilibrium position and assuming a net increase (decrease) in demand for a security, the market will eventually clear that security at some price above (below) the equilibrium price. During the process of adjustment transactions are constantly occurring as a function of demand. Under these conditions one would expect a rise in the volume of transactions with both a rise or fall in the price level. Copeland (1974) refined this theory by establishing the direction of the relationship between the absolute value of price changes and volume under two assumptions of information arrival. Using trading volume as a proxy for the rate of information arrival in the market, Copeland concludes that i the relationship is positive and linear if a hypothesis of sequential information is valid. An inverse correlation would support the notion of simultaneous information arrival. An alternative approach is to view a degree of association between price change per se and volume. The research of Ying (1966), Hsu (1973), and Epps and Epps (1976) are in this category. Illustrative of this line of reasoning Epps and Epps (E&E) developed a theory of financial markets based on a two-parameter portfolio model. Their rationale is that news reaching the market is generally accompanied by a change in the overall average of investors' expectations. And if investors are classified as either buyers or sellers (these groups are identified by their response to news entering the market) then the news reaching the market will result in changes in the average expectations of each of the two groups. Combining these two notions, the major premise of their model is that the extent of disagreement between these two groups of investors tends to increase with the absolute value of the overall average change in expectations. Building upon this assumption, E&E are able to imply that their theory (and empirical evidence) supports the notion of positive stochastic dependence between volume and security price change. In this paper additional empirical evidence is provided to support the thesis that price change per se and volume for individual securities are positively interrelated. The main methodological novelty is the use of a direct test of independence/causality developed by Haugh (1976), which is outlined in section II. In section III the results of the empirical tests are presented. The hypotheses are tested on stock data and warrant data. To date no empirical evidence has been published concerning the stochastic process generating warrant volume or the interrelationships between warrant price, warrant volume, stock price, and stock volume. Section IV contains a summary and conclusions.